2016
DOI: 10.4103/0971-3026.178360
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality imaging in cranial blastomycosis, a great mimicker: Case-based illustration with review of clinical and imaging findings

Abstract: We describe the clinical, laboratory, and imaging data of three patients who are proven cases of blastomycosis with cranial involvement. In this review, we discuss the imaging features of cranial blastomycosis with relevant clinical case examples including computed tomography (CT), magnetic resonance imaging (MRI), and advanced MR imaging techniques like magnetic resonance spectroscopy (MRS) and MR perfusion. Literature is reviewed for modern-day diagnosis and treatment of this fatal intracranial infection, if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Despite the variability between intraparenchymal and leptomeningeal lesions, MRI provides better diagnostic utility given the various reports of CT-negative findings in patients with confirmed intracranial Blastomyces . 10 The diagnostic utility of other MRI modalities has also been explored in limited studies, notably MR spectroscopy, which has shown trehalose peaks consistent with the presence of other intracranial fungomas. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the variability between intraparenchymal and leptomeningeal lesions, MRI provides better diagnostic utility given the various reports of CT-negative findings in patients with confirmed intracranial Blastomyces . 10 The diagnostic utility of other MRI modalities has also been explored in limited studies, notably MR spectroscopy, which has shown trehalose peaks consistent with the presence of other intracranial fungomas. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 10 The diagnostic utility of other MRI modalities has also been explored in limited studies, notably MR spectroscopy, which has shown trehalose peaks consistent with the presence of other intracranial fungomas. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grocott’s methenamine-silver-stained section of the same mass at ×400 magnification ( B ) with broad-based budding yeast cells. Image source is Kochar et al, 2016, used under a creative commons license (CC BY-NC-SA 3.0) [ 92 ].…”
Section: Figurementioning
confidence: 99%
“…These lesions are commonly reported in neurotuberculosis. [8910] These lesions have also been described in nocardiosis,[11] cranial blastomycosis,[12] and NCC[13] as isolated case reports. Conglomerate RELs are best seen in MRI due to its better soft-tissue resolution and multiplanar capabilities.…”
Section: Introductionmentioning
confidence: 99%